Septate junction proteins are required for cell shape changes, actomyosin reorganization and cell adhesion during dorsal closure in Drosophila - De, Oindrila; Rice, Clinton; Zulueta-Coarasa, Teresa; Fernandez-Gonzalez, Rodrigo; Ward, Robert E. (Frontiers in Cell and Developmental Biology, 2022)
Septate junctions (SJs) serve as occluding barriers in invertebrate epithelia. In Drosophila, more than 20 genes are required for the formation or maintenance of SJs. Interestingly, loss-of-function mutations in core SJ components are embryonic lethal, with defects in developmental events such as head involution and dorsal closure (DC) that occur prior to the formation of a mature SJ, indicating a role for these proteins in mid-embryogenesis independent of their occluding function. To understand this novel function in development, we examined loss-of-function mutations in three core SJ proteins during the process of DC. DC occurs during mid-embryogenesis to seal a dorsal gap in the epidermis following germ band retraction. DC is initiated by a Jun-N-terminal kinase (JNK) signaling cascade in the dorsal-most epidermal cells, ultimately leading to their elongation in the dorsal ventral axis. Closure is driven by contraction of the extraembryonic amnioserosa cells that temporarily cover the dorsal surface and by cell shape changes (elongation) of lateral epidermal cells that bring the contralateral sheets together at the dorsal midline. Using live imaging and examination of fixed tissues, we show that early events in DC occur normally in SJ mutant embryos, but during later closure, coracle, Macroglobulin complement-related and Neurexin IV mutant embryos exhibit slower rates of closure and display aberrant cells shapes in the dorsolateral epidermis. The apical surfaces of SJ mutant epidermal cells significantly differ from wild type cells in several morphological features, including dorsoventral length, aspect ratio, and surface area. SJ mutant embryos also show mild defects in actomyosin structures along the leading edge, but laser cutting experiments suggest similar tension and viscoelastic properties in SJ mutant versus wild type epidermis. In a high percentage of SJ mutant embryos, the epidermis tears free from the amnioserosa near the end of DC and live imaging and immunostaining reveal reduced levels of E-cadherin, suggesting that defective adhesion may be responsible for these tears. Supporting this notion, reducing E-cadherin by half significantly enhances the penetrance of DC defects in coracle mutant embryos.